2018
DOI: 10.24843/ejmunud.2018.v07.i07.p17
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Kompensasi, Motivasi, Dan Lingkungan Kerja Terhadap Kualitas Kerja Karyawan Pt. Delta Satria Dewata Denpasar

Abstract: Persaingan antar perusahaan di era globalisasi semakin tajam, pengembangan sumber daya manusia merupakan cara utama untuk memenangkan kompetisi global. Perusahaan memerlukan sumber daya manusia yang berkualitas yang menghasilkan kualitas kerja yang baik. Tujuan dari penelitian ini untuk menguji pengaruh kompensasi, motivasi, dan lingkungan kerja terhadap kualitas kerja kayawan dengan metode sample random sampling dalam menentukan sampel sebanyak 100 orang, melalui teknik analisis regresi linear berganda. Bedas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 1 publication
0
3
1
1
Order By: Relevance
“…A good working environment will affect the performance of its employees, and it can make a company can progress and develop following predetermined targets. The results of this study are not in line with research conducted byUmmah (2016), Wungkana (2015), Krisnayanti (2018), Ramadhani (2014), andAdrianto (2020) that the environment has a positive and significant effect on employee performance.…”
Section: Influence Of Work Environment On Employee Performancecontrasting
confidence: 99%
See 1 more Smart Citation
“…A good working environment will affect the performance of its employees, and it can make a company can progress and develop following predetermined targets. The results of this study are not in line with research conducted byUmmah (2016), Wungkana (2015), Krisnayanti (2018), Ramadhani (2014), andAdrianto (2020) that the environment has a positive and significant effect on employee performance.…”
Section: Influence Of Work Environment On Employee Performancecontrasting
confidence: 99%
“…According to previous research by Umam (2016), Wungkana (2015), Krisnayanti (2018), Ramadhani (2014), and Adrianto (2020)concluded that a comfortable and conducive work environment will optimize employee performance. In addition to the need for a good work environment, employees also need Motivation from themselves and from outside to improve performance because sometimes a sense of laziness in employees can threaten their careers.…”
Section: Introductionmentioning
confidence: 99%
“…Each worker isn't fundamentally willing to mobilize their work execution optimally, so that there's still a require for support so that somebody needs to utilize all their potential to work. This driving drive is called inspiration (Krisnayanti & Utama, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…(Ibojo et al, 2014) discovered in his research that if the rewards offered by the company to employees are changed for the better, there will be changes in satisfaction and motivation towards performance. According to (Krisnayanti et al, 2018), what can be done is to increase salaries, allowances, bonuses, allowances, and other compensations regularly to keep their spirits high and motivate them to improve their work. (Ajmal et al, 2015) demonstrated that if employees are well compensated and receive more from their colleagues, they are happier at work and can motivate an employee to improve the quality of their performance.…”
Section: H1: Work Motivation Affects Employee Performancementioning
confidence: 99%